Deutsche Gesellschaft für Sportmedizin und Prävention
Homepage of the German Association for Sportsmedicine and Prevention, contains beyond others recommendations for 10 Goldene Regeln für gesundes Sporttreiben Sport and Breast cancer Bungee-jumping Sport for persons with Endoprothesis Inline-Skating Sport and Osteoporosis Athletic activity during pregnancy Walking Sportsmedical Aspects of golfing Vaccinations for athletes Movement and Sporttherapeutical interventions in persons with depressive deseases